2003
DOI: 10.1179/135100003225003375
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell stimulation in the isolated perfused rat liver triggers nuclear factor-κB DNA binding activity

Abstract: Activation of transcription factor NF-kappaB (electrophoretic mobility shift assay) was investigated in the isolated perfused rat liver infused with 0.5 mg of colloidal carbon/ml for 5-20 min, in relation to carbon phagocytosis and carbon-induced O(2) consumption. Experiments were carried out in control rats and in animals treated with the Kupffer cell inactivator gadolinium chloride (GdCl(3)). Carbon uptake and carbon-induced O(2) consumption by perfused livers exhibited a linear increase as a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
3
1
0
Order By: Relevance
“…NF-B and STAT3 activation by T 3 administration is suppressed both by the in vivo pretreatments with -tocopherol or N-acetylcysteine (NAC) and with GdCl 3 , prior to hormone treatment. These findings support the contention that T 3 accomplishes the redox activation of hepatic NF-B and STAT3 by actions primarily exerted at the KC level [63,64], and are in agreement with the significant NF-B activation triggered by the respiratory burst of carbon-stimulated KCs found in the isolated perfused rat liver [65].…”
Section: T 3 -Induced Kupffer Cell-dependent Gene Expressionsupporting
confidence: 82%
“…NF-B and STAT3 activation by T 3 administration is suppressed both by the in vivo pretreatments with -tocopherol or N-acetylcysteine (NAC) and with GdCl 3 , prior to hormone treatment. These findings support the contention that T 3 accomplishes the redox activation of hepatic NF-B and STAT3 by actions primarily exerted at the KC level [63,64], and are in agreement with the significant NF-B activation triggered by the respiratory burst of carbon-stimulated KCs found in the isolated perfused rat liver [65].…”
Section: T 3 -Induced Kupffer Cell-dependent Gene Expressionsupporting
confidence: 82%
“…These findings are in agreement with studies showing that the NFB activation can be achieved by physiological levels of the ROS, which are produced during the respiratory burst after stimulation of isolated or cultured macrophages (Kaul & Forman, 1996) and in carbon-stimulated Kupffer cells in the isolated, perfused rat liver (Romanque et al, 2003). This may be caused by the damage produced by the oxidative stress generated by an excess of thyroid hormones.…”
Section: Hyperthyroidism and The Ros-steady Statesupporting
confidence: 81%
“…Fernandez et al found that thyroid calorigenesis is a hormonal stimulus for the REDOX activation of NFB, a response that is triggered in Kupffer cells having higher respiratoryburst activities (Fernandez et al, 2006). These findings are in agreement with studies showing that the NFB activation can be achieved by physiological levels of the ROS, which are produced during the respiratory burst after stimulation of isolated or cultured macrophages (Kaul & Forman, 1996) and in carbon-stimulated Kupffer cells in the isolated, perfused rat liver (Romanque et al, 2003). This may be caused by the damage produced by the oxidative stress generated by an excess of thyroid hormones.…”
Section: Hyperthyroidism and The Ros-steady Statesupporting
confidence: 62%